Formulation and Antioxidant Activity Test of Face Mist Preparation from Red Dragon Fruit (Hylocereus polyrhizus) Peel Ethanol Extract Using the DPPH (2,2-diphenyl-1-picryhydrazyl) Method - Fitri Wa Ode Ida Fitriah; Nur Hatidjah Awaliyah Halid; Novita Mayang Sari (Faculty of Mathematic and Natural Science, Garut University, 2026)
The natural antioxidant potential of red dragon fruit (Hylocereus polyrhizus) peel is attributed to polyphenols, flavonoids, and anthocyanins, and it can be used in cosmetic formulations as an active ingredient. This research was conducted to analyze the characteristics, physical stability, and antioxidant activity of face mist preparationscontaining ethanol extract of red dragon fruit peel. The extract was obtained by maceration with 96% ethanol as the solvent and formulated into three concentrate levels:FI (5%), FII (10%), and FIII (15%). Evaluation of the preparations was conducted using organoleptic tests, homogeneity, pH, viscosity, drying time, spray spreadability, and cycle tests, while antioxidant activity was assessed by the DPPH method. The tested formulation exhibits physical properties within an acceptable range and stability, andshows very strong antioxidant activity, with IC₅₀ values of 29.914 µg/mL, 26.510 µg/mL, and 24.259 µg/mL, respectively. FIII (15%) exhibited the strongest antioxidant activity, indicated by the lowest IC₅₀ value. Further research is recommended to evaluate longterm stability, moisture content, and potential skin irritation to support the development of natural-based cosmetics.